Engineering students' with financial need and their perceptions of success in their college experience: a phenomenological analysis - Roberts, William R., author; Kuk, Linda, advisor; Anderson, Sharon, committee member; Siller, Tom, committee member; Chesson, Craig, committee member (Colorado State University. Libraries, 2016)
The purpose of this study was to explore how engineering students at different educational levels, who have high financial need as determined by the FAFSA process, set goals and strategies to achieve what they believe to be success in their college curriculum at a medium sized mid-western polytechnic university. During this interpretive phenomenological analysis, interviews were conducted with 16 students which revealed four emergent themes and two super ordinate themes. The data from this study suggests participants focused on developing individual goals and strategies designed to learn coursework material positioning them to begin their engineering careers. The participants in the study relied upon personal support systems of family, faculty and staff member members at Superior Tech to guide them through their success journey. Although the participants were unhappy with their student loans, they indicated their career choice as an engineer would position them well for future financial stability. It appears participants considering engineering degrees will likely be inclined to make a significant investment in their educational experience if they have family encouragement, institutional support and the potential to begin a high paying career as an engineer. The study concluded with implications for practice for families of college students, financial aid practitioners, student success researchers, engineering faculty, student affairs professionals and future research possibilities.